Laparoscopic hernia repair using Lapa−Her −Closure(™) for giant pediatric subxiphoid incisional hernia - Saki Sakamoto; Naoki Hashizume; Motomu Yoshida, PhD; Shinji Ishii, PhD; Suguru Fukahori, PhD; Nobuyuki Saikusa, PhD; Daisuke Masui; Naruki Higashidate; Shiori Tsuruhisa; Yoshiaki Tanaka, PhD; Minoru Yagi, PhD (Elsevier, 2018)
We report a case of laparoscopic repair of giant subxiphoid incisional hernia (SIH) using Lapa-Her-Closure™ in a child. The patient was a 4-year-old girl with a giant SIH after median sternotomy. The orifice of the hernia was located at a midpoint between the xiphoid process and umbilicus, the size of the hernia was 6 × 1 cm, and its content was preperitoneal fat. We completed direct suture of the fascial defect laparoscopically. A Lapa-Her-Closure™ needle with a 2-0 Ethibond was passed through the right rectus muscle, the suture was placed in the abdominal cavity, only the needle was pulled back, then the needle was passed through left rectus muscle to pick up the above 2-0 Ethibond. A total of 7 sutures were put over the hernia defect at a distance of 1 cm cranially and caudally. The post-operative course was uneventful. The procedure was safe, quick, simple, and cosmetically acceptable.